2018
DOI: 10.1155/2018/7845143
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Sandstone under Cyclic Loading: Damage Assessment Using Ultrasonic Wave Velocities and Changes in Elastic Modulus

Abstract: This laboratory study investigated the damage evolution of sandstone specimens under two types of cyclic loading by monitoring and analyzing changes in the elastic moduli and the ultrasonic velocities during loading. During low-level cyclic loading, the stiffness degradation method was unable to describe the damage accumulations but the ultrasonic velocity measurements clearly reflected the damage development. A crack density parameter is introduced in order to interpret the changes in the tangential modulus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The most basic task is selecting an appropriate damage variable to characterize the damage to the rock [21,22]. Based on the principles of residual strain [23], elastic modulus [24] and P-wave velocity [25], scholars have established expressions of damage variables. The attenuation of the elastic modulus and the accumulation of residual deformation are the external manifestations of damage; they cannot quantitatively reflect the degree of damage.…”
Section: Introductionmentioning
confidence: 99%
“…The most basic task is selecting an appropriate damage variable to characterize the damage to the rock [21,22]. Based on the principles of residual strain [23], elastic modulus [24] and P-wave velocity [25], scholars have established expressions of damage variables. The attenuation of the elastic modulus and the accumulation of residual deformation are the external manifestations of damage; they cannot quantitatively reflect the degree of damage.…”
Section: Introductionmentioning
confidence: 99%
“…There are many definitions for the damage variable such as energy dissipation, maximum strain, residual strain, acoustic emission count, and ultrasonic wave velocity. A rational damage variable should accurately describe the process of rock degradation, development of microfractures, and the process of microfractures converging into macrofractures. Most damage variables indicate that rock shows a classical three-stage behavior of damage evolution under CACMS. The damage variable increases quickly in the first few cycles, which is due to the closure of microfractures in the rock specimen. Afterward, damage remains stable for a long cycling time and then increases sharply until the rock fails.…”
Section: Introductionmentioning
confidence: 99%
“…In the low-stress region, Hsieh et al [6] concluded that the stiffness of the rock will first increase due to the crack closure and then decrease when crack growth occurs after repeated loading. Yang et al [7] used the P-and S-wave velocities based on the ultrasonic wave velocity method to reflect the sandstone behaviour (i.e. elastic modulus and the shear modulus) under cyclic loading condition and found that rock specimens stiffen during loading and soften during unloading.…”
Section: Introductionmentioning
confidence: 99%